The effect of gear geometry on the thickness of tooth face hardened layer - Tököly, P.; Bošanský, Miroslav; Vanya, A. (НТУ "ХПИ", 2010)
This article describes the effect of the geometrical parameters of the standard involute and non-standard convex-concave (C-C) gearing on the thickness of the hardened layer. The thickness of hardened layer is important from the aspect of wear on gearing. In case of involute gearing is the thickness of the hardened layer defined by various authors, what is on the other hand determinated also by the standard STN 01 4686-5. In case of C-C gearing there are not available any standards, and therefore it is possible to determine the thickness of the hardened layer only by the means of modern simulation methods.

В статье описывается влияние геометрических параметров стандартных эвольвентных и нестандартных выпукло-вогнутых (CC) зубчатых передач до толщины упрочненного слоя. Толщина упрочненного слоя имеет важное значение для износа зуба. В случае с эвольвентной передачей толщина слоя определяется более авторами, и также использованием стандарта STN 01 4686-5. В случае нестандартных выпукло-вогнутых (C-C) зубчатых передач нет стандартов, поэтому можно определить толщину закаленного слоя только с использованием современных методов моделирования.
Keywords: geometrical parameters; requirements; tooth face profile; normal components; tangentional components; distribution of velocity; experimental methods; Chemical Vapour Deposition